The Influence of Original Local Government Revenue and Human Development Index on Economic Growth in Kabupaten Gowa - Arifin Arifin; Nasir Hamzah; Munawir Nasir (PT Mattawang Mediatama Solution, 2023)
This research was conducted with the aim of delving into two crucial aspects that impact economic growth in Kabupaten Gowa. The first aspect is the influence of Original Local Government Revenue. (PAD) on the economic dynamics of the region. By delving deeply into how PAD affects economic growth, this study opens up avenues for understanding the extent to which local economic resources contribute to sustainable economic development. The second aspect investigated is the role of the Human Development Index (HDI) in shaping the trends of economic growth in Kabupaten Gowa. This approach provides a broader view of economic growth, not just from a pure economic perspective but also involving social and human well-being dimensions. By examining how HDI can significantly contribute to economic growth, this research recognizes the importance of investing in human development to achieve sustainable economic outcomes. To achieve the objectives of this research, the method of multiple linear regression was employed as an appropriate approach. By combining secondary data encompassing Original Local Government Revenue (PAD), Human Development Index (HDI), and Gross Regional Domestic Product (GRDP) from the period of 2012 to 2020, this study presents a comprehensive view of the relationship between these variables. The data obtained from the Local Revenue Agency of Kabupaten Gowa provides a robust foundation for in-depth and accurate analysis. The results of the conducted multiple linear regression analysis yield valuable findings. Firstly, it is revealed that the influence of Original Local Government Revenue (PAD) on Economic Growth is positive, but it does not exhibit strong significance. However, a further understanding of how PAD can more effectively drive economic growth remains an intriguing question to explore. The second finding indicates that the Human Development Index (HDI) has a significant positive impact on Economic Growth. This underscores the importance of investing in human development, such as education, healthcare, and community empowerment, in stimulating sustainable economic progress. Overall, this research offers a deeper understanding of the economic dynamics in Kabupaten Gowa, encompassing both the aspects of Original Local Government Revenue and Human Development Index. These findings provide valuable insights for decision-making at the government and relevant institutions' levels to develop more holistic and sustainable development strategies.